Pengembangan Rubrik Analitik Penilaian Keterampilan Menulis Teks Narasi untuk Siswa Sekolah Dasar pada Kurikulum Merdeka - Ma’arif, Robi Syamsul; Apriliya, Seni; Hidayat, Syarip (PAKAR Pendidikan, 2025)
Narrative writing is important to train learners' word choice and imagination development, as well as the ability to use simple language that is easy to understand. However, teachers often find it difficult to assess learners' learning outcomes related to narrative writing skills. This study aims to design a rubric for assessing narrative text writing skills using the design-based research method (Reeves model). The steps include problem identification, solution prototype development, iterative process, and reflection. The rubric was piloted on two learners' narrative text writing and assessed by five observers. Before the pilot test, the product was validated by assessment experts (87.5% very feasible) and material experts (80% feasible). The results of the rubric trial showed the probability value of Kendall's W <0.05 (Asymp.Sig SB 0.046 and HF 0.019), indicating that the rubric can be used. In addition, the teacher response questionnaire shows that the rubric facilitates teachers in assessing learners' work in a structured, fair manner and simplifies the assessment process. The rubric also helps teachers provide more specific and targeted feedback to learners. This finding supports efforts to improve the quality of authentic assessment in the Merdeka Curriculum. Further development can be directed at digitizing the rubric to make it more practical and easily accessible. This research makes a real contribution to improving teacher competence in conducting assessments. The developed rubric can also reference other teachers who are making similar assessment instruments. Thus, the results of this study have high applicability in daily learning practices in elementary schools